KAJIAN DAN TELAAH KRITIS TAFSIR DAN HADITS TENTANG PERCERAIAN - ahsin, moh (Prodi Ahwal Al-Syakhsiyyah STAI Imam Syafi'i Cianjur, 2024)
Divorce is defined as the dissolution of the marital bond between husband and wife by using the word